Breeding strategies to improve maize for adaptation to low soil nitrogen in West and Central Africa - Ajala, S.O.; Menkir, A.; Kamara, A.Y.; Alabi, S.O.; Abdulai, M.S. (African Crop Science Society, 2007)
The moist savannas of West and Central Africa have great potential for maize grain production due to high levels of radiation and reduced incidence of pests and diseases. However, soils in this zone are generally low in organic matter and cation exchange capacity in addition to land use intensification. Improving productivity of maize in the savannas will therefore rely on improving soil fertility, ensuring efficient use of inputs and low-N tolerant maize varieties. Breeding maize for adaptation to low soil nitrogen will enhance the capacity of cultivars to use limited nitrogen more efficiently for grain production. Attempts at developing N-efficient maize genotypes for this region resulted in the identification of hybrids as having better N-use efficiency than open pollinated cultivars, identification of inbreds with high N-use efficiency and the development of prolific and low-N tolerant populations. Recurrent selection schemes whereby desirable progenies for recombination were selected based on an index that combine agronomic performance under low-N with yield under high-N to maximize gains under both environments, have been used to improve the developed populations. Evaluation of different cycles of selection showed that a minimum yield gain of 100 kg ha-1 cycle-1 under low-N is feasible. This yield gain is associated with desirable changes in other agronomic traits. Determination of relationships between vertical root pulling strength and nitrogen uptake and use efficiency and testing of maize genotypes developed for drought under low-N are other strategies that can aid breeding for tolerance to low-soil nitrogen.